A furan-derived epoxy thermoset with inherent anti-flammability, degradability, and raw material recycling. (January 2023) - Nabipour, H.; Wang, X.; Song, L.; Hu, Y.
Abstract: The production of multifunctional thermosets with flammability, degradability and raw material recycling from epoxy thermosets made from renewable resources is one of the hottest topics in the context of sustainable development. In this work, we fabricated a fully bio-based epoxy thermoset by curing an as-synthesized furan-derived epoxy monomer (HMF-DDDS-EP) with a furan-based hardener (DFA). Owing to its unique structure containing a Schiff base and disulfide bonds, the cured HMF-DDDS-EP/DFA thermoset integrates a high glass transition temperature, high tensile strength, inherent anti-flammability, degradability, and recyclability. Specifically, a glass transition temperature as high as 171 °C, tensile strength of 62.9 MPa, a storage modulus of 2, 356 MPa and outstanding anti-flammability (UL-94 V-0 rating and high LOI of 36.0%) were observed for this fully bio-based epoxy thermoset. Additionally, it was capable of degrading under mildly acidic conditions because of the cleavage of the Schiff base into the original aldehyde monomer. This fully bio-based epoxy thermoset can be considered a representative for fostering the synthesis of advanced thermosetting materials derived from renewable resources. Graphical abstract: A furan-derived epoxy thermoset (HMF-DDDS-EP/DFA) showed multi-functionilties including anti-flammability, degradability and recyclability. Image 1 Highlights: A bio-based epoxy thermoset (HMF-DDDS-EP/DFA) was synthesized from furan derivatives. HMF-DDDS-EP/DFA showed an outstanding anti-flammability (UL-94 V-0 grade and high LOI of 36.0%). HMF-DDDS-EP/DFA was capable to degrade under mildly acidic conditions. The Schiff base and disulfide bonds endowed HMF-DDDS-EP/DFA with recyclability.